1987
DOI: 10.1016/0035-9203(87)90253-7
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of alpha thalassaemia with malaria

Abstract: A controlled trial of iron dextran prophylaxis in infants 2 months old was carried out on the north coast of New Guinea, where malaria is holoendemic. These infants have a high carrier rate (80%) for alpha + thalassaemia. The neighbouring highland area has a low rate of both malaria and alpha + thalassaemia. The results of clinical and haematological examination of these infants at 6 and 12 months were analysed to determine the relationship between alpha thalassaemia and susceptibility to malaria. Infants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 9 publications
1
18
1
Order By: Relevance
“…27 It is thus feasible that while α + -thalassemic children acquire less infections, they are less able to control parasite densities at low level and the infections that do occur are more likely to become LM-patent and become symptomatically unwell. This explanation however runs counter to evidence from earlier studies from the Pacific that suggested that the incidence of malaria might be raised in the youngest children with alpha thalassemia 10,28 and that α + -thalassemia does not affect the acquisition of antibodies to variant surface antigens (VSA). 9,12 Further studies of the combined effects of α + -thalassemia and acquired immunity on risk of P. falciparum infection and illness are thus warranted.…”
Section: Discussioncontrasting
confidence: 77%
“…27 It is thus feasible that while α + -thalassemic children acquire less infections, they are less able to control parasite densities at low level and the infections that do occur are more likely to become LM-patent and become symptomatically unwell. This explanation however runs counter to evidence from earlier studies from the Pacific that suggested that the incidence of malaria might be raised in the youngest children with alpha thalassemia 10,28 and that α + -thalassemia does not affect the acquisition of antibodies to variant surface antigens (VSA). 9,12 Further studies of the combined effects of α + -thalassemia and acquired immunity on risk of P. falciparum infection and illness are thus warranted.…”
Section: Discussioncontrasting
confidence: 77%
“…Parasitised ␣ ϩ -thalassaemic erythrocytes bound greater levels of antibody from malaria endemic sera (25) and were more readily phagocytosed by blood monocytes (26) compared with control cells. A greater frequency of malaria in young children with thalassemia than normals has been found both in Papua New Guinea (27) and Vanuatu (28). In the latter study, P. vivax was increased particularly in children aged Ͻ30 months, and it was proposed that this increase may act as a natural vaccine against (Table 1).…”
Section: Discussionmentioning
confidence: 78%
“…To date, such descriptions have proved confusing. For example, although α + -thalassaemia confers protection against both severe [ 14, 21, 22] and fatal [ 14] malaria, until now the evidence has tended to suggest a raised, rather than a reduced, incidence of uncomplicated malaria in such children [ 24, 25]. Furthermore, data from a case-control study conducted in Papua New Guinea suggested that the selective advantage of α + -thalassaemia may not be confined to malaria, but may also extend to other diseases [ 21].…”
Section: Discussionmentioning
confidence: 99%